Risk and the importance of absent symptoms in constructions of the 'cancer candidate'. (18th August 2022) - Dobson, Christina; Russell, Andrew; Brown, Sally; Rubin, Greg
Abstract : Cancer is a disease that is imbued with notions of risk, with individuals expected to avoid 'risky' behaviours and act swiftly when symptoms indicating a risk of cancer emerge. Cancer symptoms, however, are often ambiguous and indicative of a number of other conditions, making it difficult for people to assess when symptoms may, or may not, be the result of cancer. Here, we discuss interview data from a study examining the symptom appraisal and help-seeking experiences of patients referred for assessment of symptoms suspicious of a lung or colorectal cancer in the North-East of England. We explore how individuals draw upon ideas about cancer risks to assess whether cancer may be a possible explanation for their symptoms and to inform their decisions about help-seeking. In our analysis, we applied the concept of candidacy to the data, to highlight how lay epidemiology shapes people's perceptions of cancer risk, and their subsequent responses to it. We found that participants appraised their symptoms, and the likelihood that they may have cancer, in light of relevant information on risk. These sources of information related to lifestyle factors, family history of cancer, environmental factors, and importantly, the symptomatic experience itself, including the absence of symptoms that participants associated with cancer. The importance of experienced, and absent, symptoms was a core element of participants' everyday constructions of the 'cancer candidate', which informed symptom appraisal and subsequent help-seeking decision-making.